Genetic variation of Boesenbergia rotunda (L.) Mansf. from Thailand based on essential oil compositions and internal transcribed spacer sequences - Orawan Theanphong (2022)
Boesenbergia rotunda (Zingiberaceae), an aromatic perennial herb, has been used in ethnomedicine as an antiflatulent, antidiarrheal, and antirheumatism agent. In this study, the genetic variation of three types of B. rotunda from Thailand, one wild type (‘Krachai Pha’) and two cultivars (‘Krachai Ban’ and ‘Krachai Deang’), was studied by analyzing the essential oil compositions of their roots and rhizomes together with their internal transcribed spacer (ITS) sequences. The roots and rhizomes of ‘Krachai Ban’ and ‘Krachai Pha’ were rich in monoterpene hydrocarbons and oxygenated monoterpenes whereas the roots and rhizomes of ‘Krachai Deang’ were rich in oxygenated monoterpenes. The results of phylogenetic analysis based on the essential oil compositions and ITS sequences showed that ‘Krachai Ban’ was more closely related to ‘Krachai Pha’ than to ‘Krachai Deang’. It should be concluded that three types of B. rotunda from Thailand might be potential sources for drug discovery.